Pliocene Warmth Consistent With Greenhouse Gas Forcing - Jessica E. Tierney; Alan M. Haywood; Ran Feng; Tripti Bhattacharya; Bette L. Otto‐Bliesner (Geophysical Research Letters, 2019)
Abstract With CO2 concentrations similar to today (410 ppm), the Pliocene Epoch offers insights into climate changes under a moderately warmer world. Previous work suggested a low zonal sea surface temperature (SST) gradient in the tropical Pacific during the Pliocene, the so‐called “permanent El Niño.” Here, we recalculate SSTs using the alkenone proxy and find moderate reductions in both the zonal and meridional SST gradients during the mid‐Piacenzian warm period. These reductions are captured by coupled climate model simulations of the Pliocene, especially those that simulate weaker Walker circulation. We also produce a spatial reconstruction of mid‐Piacenzian warm period Pacific SSTs that closely resembles both Pliocene and future, low‐emissions simulations, a pattern that is, to a first order, diagnostic of weaker Walker circulation. Therefore, Pliocene warmth does not require drastic changes in the climate system—rather, it supports the expectation that the Walker circulation will weaken in the future under higher CO2.